Pemanfaatan Media Sosial Instagram Untuk Digital Marketing Pada UMKM Bakso Dan Es Campur “Family” Di Kota Blitar - Gading Wijaya, Salsa Febiola; Faulia Rahma, Riska; Bahrul Ulum, Krisna; Setyo Budiwitjaksono, Gideon; Marthina Rosyanti, Daisy; Abuzar Zuhri, M. Fernanda (Universitas Gajah Putih, Indonesia, 2023)
The advancement of technology has a significant impact on human existence, and one example of this is information technology, which offers a variety of advantages to the process of creating a business. The information technology in question is known as digital marketing, and its primary purpose is to promote the dissemination of commercial items through various online media, including social media platforms like Instagram. This service takes a comprehensive approach by way of the socialisation component of the intense approach method. According to the findings of this service, there are a number of promotional activities that are carried out by Bakso & Es Campur